2018
DOI: 10.1002/jcp.27689
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of human mesenchymal stem cells derived beta cell precursors on a nanofibrous scaffold: An approach to treat diabetes mellitus

Abstract: Diabetes mellitus is an autoimmune and chronic disorder that is rapidly expanding worldwide due to increasing obesity. In the current study, we were able to design a reliable 3‐dimensional differentiation process of human Wharton's jelly mesenchymal stem cells into pancreatic beta cell precursors (PBCPs) and detected that transplanted PBCPs could improve hyperglycemia in a diabetes‐induced model in mice. Polylactic acid/chitosan nanofibrous scaffold was prepared using an electrospinning method. Quantitative re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
(48 reference statements)
1
7
0
Order By: Relevance
“…While compared to the PKH26-3D-Exo, PKH26-2D-Exo showed a remarkably less accumulation at the same time in the liver. This strongly suggests that an enhancing antifibrotic efficacy is maximized by exosomes that contain different bioactive molecules (miRNAs, proteins, and lipids) accumulating at the intended site [36,37]. This has been found in other systems.…”
Section: Discussionmentioning
confidence: 59%
“…While compared to the PKH26-3D-Exo, PKH26-2D-Exo showed a remarkably less accumulation at the same time in the liver. This strongly suggests that an enhancing antifibrotic efficacy is maximized by exosomes that contain different bioactive molecules (miRNAs, proteins, and lipids) accumulating at the intended site [36,37]. This has been found in other systems.…”
Section: Discussionmentioning
confidence: 59%
“…HG and high oxidative stress may damage the function of transplanted stem cells in patients with diabetes, which makes the effect of MSC therapy unsatisfactory (25). The present results indicated that HG increased MSC apoptosis and inhibited MSC paracrine function.…”
Section: Discussionmentioning
confidence: 65%
“…As chemical-based differentiation can aid in the expression of the key functional genes during differentiation, the cells will be able to perform functionally equivalent to mature beta cells after transplantation [127]. Nevertheless, immature pancreatic cells from mesenchymal cells (FoxA2+/PDX1+/NKX6.1+) transplanted in diabetic mouse were able to integrate and differentiate into mature cells (INS+) and rapidly reverse the disease condition [128]. Likewise, differentiated beta cell-like cells from the donor MSC can integrate, survive, and efficiently function after the clinical transplantation in patients.…”
Section: Resultsmentioning
confidence: 99%